Editorial - Ferraro, Speranzina (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
"Future Guidance" is the theme of this call, a theme we consider central in the current landscape. But why future orientation and why centrality of orientation? And above all: what orientation for the future? These are some of the questions that the call has brought to the attention of interested authors, together with a reflection on the society in which we live. The entry of the new millennium has brought radical changes in society, in the world of work, in the way we live and relate to each other, in the way we communicate and in the economy. In addition, increasingly advanced and innovative technologies are permeating people's lives and have become indispensable in everyday life, as well as in professional life, changing the way we relate to others. These radical changes have contributed to the introduction of disruption and uncertainty into people's lives, to the extent that the perception of ‘being on the move’ is becoming more and more important. people's lives, so much so that the perception of ‘precariousness’ has become a constant in the lives of both young people and adults.